Effects of environmental colour on growth of Nile tilapia, Oreochromis niloticus (Linnaeus, 1758), maintained individually or in groups - Luchiari, A. C. [UNESP]; Freire, F. A. M. [UNESP] (Wiley-Blackwell Publishing, Inc, 2009)
Examined was the influence of different colours of light on the growth of adult Nile tilapia (Oreochromis niloticus) held either individually (initial size 12.8 +/- 1.1 cm; 62.9 +/- 15.6 g) or in groups (initial size 7.8 +/- 0.8 cm; 17.2 +/- 6.4 g). Various colours (blue 434.5 nm, violet 430.0 nm, red 609.7 nm, green 525.2 nm and yellow 545.2 nm) did not affect weight gain of fish held individually (initial to final weights: blue 62.5 +/- 18.4 to 72.9 +/- 16.0 g, violet 63.5 +/- 17.8 to 78.0 +/- 19.1 g, green 62.1 +/- 13.0 to 72.9 +/- 15.7 g, and yellow 60.4 +/- 20.4 to 71.0 +/- 21.1 g); red seemed to restrict growth (initial to final weights: 65.8 +/- 13.3 to 71.8 +/- 10.8 g). Final weight differences were observed among individuals in groups maintained under blue, violet, red and green light (smaller and larger fish: blue 13.2 +/- 5.0 and 18.9 +/- 7.0 g, violet 17.3 +/- 5.2 and 23.8 +/- 4.7 g, red 14.7 +/- 3.3 and 23.9 +/- 4.7 g, and green 19.4 +/- 7.8 and 28.6 +/- 8.1 g); however, under the yellow light there were no differences in final weights (smaller fish 19.1 +/- 4.8 g; larger fish 26.2 +/- 5.2 g). Under the red light, heterogeneity in growth was observed earlier than with the other colours. It is therefore suggested that the red colour might have some harmful effects on Nile tilapia growth, limiting weight gain when fish are individually maintained, and with weight differences increasing when fish are held in groups. on the other hand, the yellow light seems to be positive for Nile tilapia, as it appears not to affect individually-held fish, but reduces variation in growth of group-maintained fish, promoting growth homogeneity.